Synthesis of poly(propylene carbonate) from highly active, inexpensive achiral (Salph)Co(III)X as initiator and bis(triphenyl phosphine) iminium as co-initiator - Narang S.; Macova E.; Berek D.; Upadhyay S.N.; Mehta R. (My University, 2025)
Copolymerization of carbon dioxide with racemic propylene oxide has been investigated in the presence of an inexpensive achiral (Salph)Co(III)X [Salph is N,N′-bis(3,5-di-tert-butylsalicylidene) phenylenediimine and X is pentaflorobenzoate] as initiator and [PPN]+Cl- ([PPN] is bis(triphenylphosphine) iminium) as co-initiator. Effects of monomer-to-initiator ratio, initiator/co-initiator ratio, and reaction conditions like stirring rate, temperature, and pressure of CO2 on the molecular weight, yield, and selectivity of poly(propylene carbonate) over propylene carbonate have been studied. The initiator used in the study has been found to be highly active at milder conditions of pressure and temperature, giving a product with maximum Mw of 14.8 × 103 g/mol at 25 bar and 50C. The conversion increases with an increase in stirring rate and then becomes almost constant at 1100 rpm and above, indicating that the reaction is no longer limited by mass transfer. The molecular weight Mw of the polymer has been found to increase with increasing monomer-to-initiator ratio up to 3000:1, but it starts decreasing with a further increase in monomer-to-initiator ratio, giving a polymer of lower Mw. The activity of the initiator is considerably affected by pressure, temperature, time, and amount of co-initiator. The polymeric product has low polydispersity (near unity) with negligible formation of polypropylene oxide. © 2015 Wiley Periodicals, Inc.